Friction stir welding of glass fiber-reinforced polyamide 6: Analysis of the tensile strength and fiber length distribution of friction stir welded PA6-GF30. (February 2019) - Meyer, S P; Jaeger, B; Wunderling, C; Zaeh, M F
Abstract: Friction stir welding (FSW) is a solid state welding process that is preferably used for aluminum alloys. In the study described here, FSW was applied to glass fiber-reinforced polyamide 6 (PA 6) and evaluated in terms of weld strength and fiber length distribution in the weld seam. For this purpose, the main effects on the tensile strength for friction stir welded specimens with a stationary shoulder were investigated. It could be shown that small tilt angles in combination with high contact pressures are advantageous. Using the optimum settings, a tensile strength of 50% of the base material strength could be achieved. Furthermore, an optical measuring method for large-volume fiber length measurement is introduced and evaluated. It has been demonstrated that the fibers shorten during the process. However, this has only a minor influence on the strength, while the influence of the tilt angle, the contact pressure, and the feed rate are significant.